Rodinian devil in disguise: Correlation of 1.25-1.10 Ga strata between Tasmania and Grand Canyon - Mulder, J.; Karlstrom, K.; Halpin, J.; Merdith, A.; Spencer, Christopher; Berry, R.; McDonald, B. (Geological Society of America, 2018)
Locating the continuation of the ca. 1.30-1.00 Ga Grenville orogen on continents formerly adjacent to Laurentia is central to resolving the paleogeography of the supercontinent Rodinia. Here we emphasize a correlation of late Mesoproterozoic foreland basins that, prior to truncation by Neoproterozoic rift margins, may have extended west of Laurentia within Rodinia. We propose correlation of the Unkar Group (Grand Canyon, Arizona, USA) with the upper Rocky Cape Group (Tasmania, southeast Australia) based on their similar stratigraphy, 1.25-1.10 Ga depositional age, and detrital zircon U-Pb age distribution and Hf isotope composition. This correlation places Tasmania adjacent to southwest Laurentia in the late Mesoproterozoic, which supports a new paleogeographic model for Rodinia. In this model, Tasmania and crustal fragments of Laurentia comprising the South Tasman Rise and the Coats Land block form key links between the Grenville orogen in southwest Laurentia and the Maud orogen (East Antarctica). A 1.14-1.07 Ga connection between the combined Grenville-Maud orogen and the Musgrave orogen of central Australia is compatible with paleomagnetic data but requires ~4000 km of relative motion between Australia-Antarctica and Laurentia prior to the final assembly of Rodinia at ca. 0.90 Ga. We hypothesize that the final assembly of Rodinia was achieved by dextral motion between the crust of Australian and Laurentian affinity along a plate boundary concealed beneath ice cover in East Antarctica.